Issues, Challenges and Prospects of Small and Medium Scale Enterprises (SMEs) in Port-Harcourt City, - Okechukwu Agwu, Mba; Izunwanne Emeti, Cletus (European Journal of Sustainable Development, 2014)
The paper discussed Issues, Challenges and Prospects of Small and Medium Scale Enterprises (SMEs) in Port-HarcourtCity, Nigeria.This was informedbythe high rate of unemployment in the society and the poor performance of SMEs in employment generation. While the research questions addressed theextent to which poorfinancing, inadequate social infrastructures, lack of managerial skills and multiple taxation constitute major challenges in the performance of SMEsbetween October 2012 and November 2013, it assumes that government intervention throughthe provision of financial assistance, social infrastructures and favorable taxation policies will reverse the trend.The paper adopted descriptive research design using 120 randomly selectedregistered operators of SMEs in Port-Harcourt City.Data collected were analyzed using descriptivestatistics while formulated hypotheses were tested using z-test. Results from the data analysis indicated thatpoor financing, inadequate social infrastructures, lack of managerial skills and multiple taxation were major challenges confronting SMEs in Port-Harcourt City,thus recommended: provision of soft loans to SMEs operators,government guaranteeing of long-term loans to SMEs operators, establishment of SMEsfunding agency,public/private sector partnership in infrastructural provision,capacity building for SMEs operators and provision of tax incentives for SMEs operators. Keywords: Small and Medium Scale Enterprises,SME operators,Port-Harcourt City, Nigeria.